2023
DOI: 10.3390/en16020787
|View full text |Cite
|
Sign up to set email alerts
|

Electricity and Heat Demand in Steel Industry Technological Processes in Industry 4.0 Conditions

Abstract: The publication presents heat and electricity management in the Polish steel industry. The paper is based on actual data on heat and electricity consumption and intensity by processes in the steel industry in Poland in Industry 4.0 conditions. Two steel production processes are used in Poland: EAF Electric Arc Furnace and BOF Basic Oxygen Furnace. The analysis is an analysis of actual data is used to characterise the electricity and heat consumption by processes in the Polish steel industry. The analysis shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Eurostat reported that at the end of 2022, inflation in the EU (Eurozone) was 9.2% and in the EU as a whole over 11% [100]. The largest contributor to price increases was energy, which reduced production in the steel sector, which is highly energy-intensive [101,102]. In Poland, almost 50 per cent of steel is tipped in EAF technology, and the other half in BOF technology [98].…”
Section: Discussionmentioning
confidence: 99%
“…Eurostat reported that at the end of 2022, inflation in the EU (Eurozone) was 9.2% and in the EU as a whole over 11% [100]. The largest contributor to price increases was energy, which reduced production in the steel sector, which is highly energy-intensive [101,102]. In Poland, almost 50 per cent of steel is tipped in EAF technology, and the other half in BOF technology [98].…”
Section: Discussionmentioning
confidence: 99%
“…Smart buildings are designed to intelligently manage energy consumption by utilizing sensors and automation systems [45]. These technologies ensure that lighting [46], heating [47], and cooling systems [48] are only active when necessary, leading to reduced energy waste [48]. Moreover, smart buildings often incorporate renewable energy sources such as solar panels [49] and efficient insulation materials, further contributing to a sustainable future [50].…”
Section: Active Small Consumers In the Energy Marketmentioning
confidence: 99%
“…The largest technological changes will be implemented in sectors that use coal, such as the steel sector [5][6][7][8]. The investments realised by manufacturers strongly reduced the energy intensity of production [9,10], although many manufacturers stopped investments after the COVID-19 pandemic [11] but proceeded again to build sustainability, both using digital technologies [12] and participating in deep decarbonisation [13]. Coal is also a source of energy that is recognised as black.…”
Section: Introductionmentioning
confidence: 99%